2018
DOI: 10.1063/1.5044752
|View full text |Cite
|
Sign up to set email alerts
|

A table-top EUV focusing optical system with high energy density using a modified Schwarzschild objective and a laser-plasma light source

Abstract: For investigating extreme ultraviolet (EUV) damage on optics, a table-top EUV focusing optical system was developed in the laboratory. Based on a modified Schwarzschild objective with a large numerical aperture and a laser-plasma light source, this optical system can generate a focusing spot with the maximum energy density of 2.27 J/cm2 at the focal plane of the objective at the wavelength of 13.5 nm. The structures and the characterized properties of this optical system are presented in this paper. For testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this domain, reflective and diffractive type elements are generally employed. Multi-layers coated on typical reflective faces are helpful in achieving an acceptable reflectivity and optical aberration [6]. For the wavelength range of 35-50 nm, Sc/Si multi-layer is suitable.…”
Section: Introductionmentioning
confidence: 99%
“…In this domain, reflective and diffractive type elements are generally employed. Multi-layers coated on typical reflective faces are helpful in achieving an acceptable reflectivity and optical aberration [6]. For the wavelength range of 35-50 nm, Sc/Si multi-layer is suitable.…”
Section: Introductionmentioning
confidence: 99%
“…High-numerical-aperture (high-NA) optical systems are most suitable for performing such tests in a laboratory owing to the high fluence of EUV radiation [6,7]. Using the simplest high-NA optical system consisting of two mirrors [7], a tabletop EUV focusing optical system with an operational wavelength of 13.5 nm was developed at the Institute of Precision Optical Engineering (IPOE) for investigating the damage of optical elements caused by EUV radiation [8]. This optical system contains a modified Schwarzschild objective [5] with an NA of 0.44 and two mirrors with the same radius of curvature (RoC) equal to 143.82 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of optical devices for light-shape focusing in the EUV region hinders their application in high-performance radiation facilities.To date, several methods exist for focusing EUV radiation into a single point. The functions and characteristics of Schwarzschild mirrors coated by multiple layers (e.g., Sc/Si for 46.9 nm and Mo/Si for 13.5 nm) exhibit a relatively high reflectivity at normal incidence based on the Prague formula; they are more suitable for focusing EUV radiation into a tight focus 19,20 . Fresnel-zone plates (FZP) provide more flexible EUV light focusing to a certain extent 21 ; however, the spatial resolution of FZP is on the order of the width of its outermost zone.Recently, Ossiander et al demonstrated that a metalens could efficiently focus vacuum-guided EUV light 22 .…”
mentioning
confidence: 99%